Evaluation of the Microbial Safety of Child Food of Animal Origin in Greece. Issue 3 (7th February 2014) - Liandris, Emmanouil; Gazouli, Maria; Taka, Styliani; Andreadou, Margarita; Vaiopoulou, Anna; Tzimotoudis, Nikolaos; Kasampalidis, Ioannis; Mpaseas, Dionysis; Fyliousis, George; Poltrionieri, Palmiro; Cook, Nigel; Ikonomopoulos, John
Abstract Foodborne illness is a major cause of morbidity and mortality especially for children, even in the developed world. The aim of this study was to assess the microbial safety of food of animal origin intended for consumption by children in Greece. Sampling involved 8 categories of retail products and was completed with a collection of 850 samples. These were tested by PCR and/or culture for Listeria monocytogenes, Campylobacter spp., Escherichia coli O157, Salmonella spp., Cronobacter sakazakii, Brucella spp., and Mycobacterium avium subsp paratuberculosis (MAP). The number of positive results recorded collectively for the pathogens under investigation over the total number of samples tested was 3.52% and 0.12% by PCR and culture, respectively. The most frequently detected pathogen was enterohemorrhagic E. coli (1.29%) followed by Brucella (0.82%) and Listeria (0.82%). DNA belonging to MAP was detected in 0.35% of samples, which was also the percentage of positivity recorded for Campylobacter. The percentage for Salmonella was 0.12%. It can be concluded from the results that there is no indication of noncompliance for the tested food samples. However, detection of DNA belonging to pathogens that are transmissible to humans through food is indicative that constant vigilance regarding food safety is an absolute necessity.